2022
DOI: 10.1101/2022.05.10.22274919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Too much to mask: determinants of sustained adherence to COVID-19 preventive measures among older Syrian refugees in Lebanon

Abstract: Lebanon has battled the COVID-19 pandemic in the midst of an economic crisis. The evolution of the pandemic and a fragile health system have meant that public health policy has had to rely heavily on non-pharmaceutical interventions for disease control. However, changes in disease dynamics and pandemic fatigue have meant that disease control policies need to be updated. Identifying variables associated with adherence to non-pharmaceutical preventive practices, particularly for vulnerable groups, can therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This was a cross-sectional study nested within a multiwave longitudinal study that aimed to examine the vulnerabilities of older Syrian refugees residing in Lebanon during the COVID-19 pandemic . The study included Syrian refugees aged 50 years and older who were identified from a full listing of beneficiary households of a nongovernmental humanitarian organization (the Norwegian Refugee Council).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a cross-sectional study nested within a multiwave longitudinal study that aimed to examine the vulnerabilities of older Syrian refugees residing in Lebanon during the COVID-19 pandemic . The study included Syrian refugees aged 50 years and older who were identified from a full listing of beneficiary households of a nongovernmental humanitarian organization (the Norwegian Refugee Council).…”
Section: Methodsmentioning
confidence: 99%
“…The survey was cocreated by academics, humanitarian actors, local government officials, and focal points from the refugee communities. The questionnaire was piloted internally with data collectors and local community focal points to ensure face validity . Trained data collectors administered the surveys in Arabic and entered data into structured electronic data collection forms hosted on KoBoToolbox.…”
Section: Methodsmentioning
confidence: 99%